Opposite roles of MAPKKK17 and MAPKKK21 against Tetranychus urticae in Arabidopsis - Romero-Hernandez, Gara; Martinez, Manuel (Frontiers in Plant Science, 2022)
After recognizing a biotic stress, plants activate signalling pathways to fight against the attack. Typically, these signalling pathways involve the activation of phosphorylation cascades mediated by Mitogen-Activated Protein Kinases (MAPKs). In the Arabidopsis thaliana-Tetranychus urticae plant-herbivore model, several Arabidopsis MAP kinases are induced by the mite attack. In this study, we demonstrate the participation of the MEKK-like kinases MAPKKK17 and MAPKKK21. Leaf damage caused by the mite was assessed using T-DNA insertion lines. Differential levels of damage were found when the expression of MAPKKK17 was increased or reduced. In contrast, reduced expression of MAPKKK21 resulted in less damage caused by the mite. Whereas the expression of several genes associated with hormonal responses did not suffer significant variations in the T-DNA insertion lines, the expression of one of these kinases depends on the expression of the other one. In addition, MAPKKK17 and MAPKKK21 are coexpressed with different sets of genes and encode proteins with low similarity in the C-terminal region. Overall, our results demonstrate that MAPKKK17 and MAPKKK21 have opposite roles. MAPKKK17 and MAPKKK21 act as positive and negative regulators, respectively, on the plant response. The induction of MAPKKK17 and MAPKKK21 after mite infestation would be integrated into the bulk of signalling pathways activated to balance the response of the plant to a biotic stress.